Why do firms terminate their overfunded pension plans? - Thomas, Jacob K. (Journal of Accounting and Economics, 1989)
Financial and pension variables are analyzed to test predictions of a number of explanation for the recent surge in reversions of excess assets from terminations of overfunded pension plans. Terminations are apparently motivated by cash needs, rather than tax, accounting, or wealth transfer considerations. These cash needs arise from large unexpected declines in funds from operations or financial restructuring subsequent to hostile takeover attempts. However, terminations appear to be a costly source of funds, since firms seek funds from numerous other sources (dividend cuts, ‘slow’ withdrawals of pension assets, and investment cuts) before resorting to terminations.